Factors associated with severe leptospirosis in Khonkaen Province, Thailand - Kaewpa, Kanokwan, 1972-
This population-based case-control studied the epidemiology of leptospirosis and determined the risk factors associated with its severity in Khonkaen province, Thailand from 1999 to 2000. The data came from the passive surveillance data of the epidemiology section, Khonkaen Provincial Health Office (KKPHO) and hospital records of twenty-one hospitals within Khonkaen province of Thailand.The results showed that among the 2,188 serologically confirmed cases of leptospirosis, 658 (30.1%) were severe cases and 1,530 (69.9%) were non-severe cases. Those who lived in the rural areas had less risk of severe leptospirosis compared with those who lived in the urban areas (OR 0.67, 95% CI:0.47-0.96).Those who started treatment late (> 2 days) were more at risk of severe leptospirosis than those who started treatment early (< 2 days) whether they were farmers or not. The results also showed that among those who started the treatment late (> 2 days), the farmers had less risk compared to non-farmers. Moreover, those who were less than 36 years old had risk of severe leptospirosis 1.27 times compared to those who were older (95% CI: 1.05-1.54).These results are useful to health administrators and educators in planning the content and strategies for health promotion in the prevention and control of the disease, specifically starting proper treatment early in order to prevent the severe form of the disease, among others.
Typescript.
Vita.
Thesis (MS Epidemiology, Public Health) -- University of the Philippines, Manila
Keywords: Leptospirosis -- Thailand